Potential biological application of silver nanoparticles synthesized from Citrus paradisi leaves - Naseem Akhter; Musarat Batool; Asma Yaqoob; Muhammad Shahid; Faqeer Muhammad; Jallat Khan; Muhammad Ahmad Mudassir; Majeeda Rasheed; Sana Javed; Dunia A. Al Farraj; Inshad Alzaidi; Rashid Iqbal; et al. (Scientific Reports)
Abstract Developing sustainable and eco-friendly methods for nanoparticle (NP) production in an era of environmental consciousness is crucial. This study introduces a novel approach to synthesizing silver (Ag) NPs using Citrus paradisi leaves extract (CPLE) as a green precursor at optimum conditions of the AgNO3 (2 mM) with CPLE in 1:3 ratio, at pH 14 and 80 °C temperature for reaction time of 4 h. The CP@AgNPs were formed and stabilized by Naringen, a major Citrus paradisi component. CP@AgNPs were thoroughly characterized through ultraviolet−visible (UV−vis) and Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD) analysis, and field emission scanning electron microscopy (FE-SEM) imaging techniques. CP@AgNPs demonstrated SPR peak at 450 nm, face cubic crystal structure, the average size of 8 nm, rod-shaped particle adsorbed on quasi-spherical shaped agglomerated NPs, significantly impacting both environmental and biomedical fields. In the catalytic degradation experiment, an application for environment pollutant reducer, CP@AgNPs, achieved an impressive 85% degradation efficiency of the methyl orange (MO) dye, showcasing their potential as a sustainable solution for wastewater treatment. Additionally, CP@AgNPs exhibited potent anti-biofilm properties, with half maximal inhibitory concentration (IC50) values of 0.13 and 0.12 mg/ml against Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus), respectively, indicating their promise in addressing biofilm-related issues in healthcare and industrial settings. CP@AgNPs also displayed exceptional antioxidant potential with IC50 values of 2.02, 0.07, and 0.035 mg/ml for CPLE, CP@AgNPs, and ascorbic acid, respectively, in scavenging DPPH radical, suggesting their utility in biomedical applications for mitigating oxidative stress. Notably, the bio-activity results of CP@AgNPs surpassed those of CP leaf extract, highlighting the enhanced properties achieved through this green synthesis approach. This study provides a sustainable and environmental remediation to biomedical science.